Reduced Placental Taurine Transporter (TauT) Activity in Pregnancies Complicated by Pre-eclampsia and Maternal Obesity - Desforges, Michelle (Adv Exp Med Biol, 2013)
Taurine is an important nutrient in intrauterine life, being required for fetal organ development and cellular renewal of syncytiotrophoblast (STB), the nutrient transport epithelium of the placenta. As taurine is conditionally essential in human pregnancy, the fetal and placental demand for taurine is met by uptake from maternal blood into STB through the activity of TauT. Pre-eclampsia (PE) and maternal obesity are serious complications of pregnancy, associated with fetal growth restriction (FGR) and abnormal renewal of STB, and maternal obesity is a major risk factor for PE. Here we test the hypothesis that STB TauT activity is reduced in maternal obesity and PE compared to normal pregnancy. STB TauT activity, measured in fragments of placental tissue, was negatively related to maternal BMI over the range 18–46 kg/m(2) in both the first trimester (7–12 weeks gestation) and at term (p < 0.01; linear regression). Neither TauT activity nor expression in the first trimester differed to normal pregnancy at term. STB TauT activity was significantly lower in PE than normal pregnancy (p < 0.01). Neuropeptide Y (NPY), a protein kinase C (PKC) activator which is elevated in PE and obesity, reduced STB TauT activity by 20% (50 pM–50 nM: 2 h) (p < 0.03). Activation of PKC by phorbol 12-myristate-13-acetate (1 μM) reduced TauT activity by 18% (p < 0.05). As TauT activity is inhibited by phosphorylation, we propose that NPY activates PKC in the STB which phosphorylates TauT in PE and maternal obesity. Reduced TauT activity could contribute to dysregulated renewal of STB and FGR that are common to PE and maternal obesity.